Topography and forest composition affecting the variability in fire severity and post-fire regeneration occurring after a large fire in the Mediterranean basin - Broncano, M J; RETANA, J (INTERNATIONAL JOURNAL OF WILDLAND FIRE, 2004)
This study relates the spatial variability in tree regeneration generated by fire with topography and pre-fire vegetation composition, and analyses how the pattern of fire severities determines post-fire regeneration of the dominant tree species (Pinus halepensis and Quercus ilex) in a large fire that occurred in north-eastern Spain in summer 1994. At the fire level, the proportion of the different fire severities in the burned area was characteristic of large fires that burn with high severity. At the level of plot, the variability of fire severity in the study site depended on two topographic characteristics: elevation and aspect. Plots burned with high fire severity were distributed at higher altitude than less severely burned plots, which were mainly distributed in south- and east-facing slopes. Fire severity also increased with Q. ilex density in the stand. The mosaic of fire severities determined both plant mortality and seedling regeneration. Mortality of stems caused by fire was very high in both species, but many Q. ilex individuals resprouted after fire. Seedling regeneration of P. halepensis showed large differences among plots in the burned area, reflecting large spatial variability due to the elevation gradient, the variation in density of adult pine trees, and the spatial variability created by fire.
Keywords: mortality; post-fire regeneration; resprouting